Pengaruh Teknik Expressive Writing Dalam Konseling Kelompok Terhadap Kemampuan Mengelola Marah - Amatullah, Salwa; Tawil, Tawil; Putro, Hijrah Eko (Universitas Muhammadiyah Magelang, 2021)
Abstract: This Researchiniaimed to test the effect of expressive writing techniques in group counseling on the This type research is quasi experiment with the design of the research is nonequivalent control group design, Subjects selected by purposive sampling. Sample articles used as many as 12 grade VII E students, 6 students as an experimental group and 6 students as a control group. Data collection instruments used is a questionnaire manages anger. Test this hypothesis using parametric analysis its paired sample t test and independent sample t test, test with SPSS 16.0 for Windows. The results showed that group counseling techniques expressive writing techniques in group counseling on the ability to manage anger, this is evidenced by the results of the experimental group paired sample t test with probability Sig. (2-tailed) 0,000<0,05. Based on the analysis of the average increase in the experimental group 12,78% while avarage in the control group 3,05%. In conclusion,the use of group expressive writing techniques influential to manage anger.